Helicobacter pylori infection altered gastric microbiota in patients with chronic gastritis - Hua, Zhaolai; Xu, Le; Zhu, Jiahui; Xiao, Ling; Lu, Bin; Wu, Jianping; Wu, Zhenfeng; Zhou, Qihai; Zhang, Junfeng (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: The present study aims to investigate the effect of Helicobacter pylori (Hp) infection on gastric mucosal microbiota in patients with chronic gastritis.Here recruited a population of 193 patients with both chronic gastritis and positive rapid urease, including 124 patients with chronic atrophic gastritis (CAG) and 69 patients with chronic non-atrophic gastritis (nCAG). Immunoblotting was used to detect four serum Hp antibodies (UreA, UreB, VacA and CagA) to determine the types of virulent Hp-I and avirulent Hp-II infections. Gastric microbiota was profiled based on 16S rRNA gene V3-V4 region, and R software was used to present the relationship between the microbial characteristics and the type of Hp infection.In the stomach of patients with Hp-positive gastritis, the dominant gastric bacterial genera included Ralstonia (23.94%), Helicobacter (20.28%), Pseudonocardia (9.99%), Mesorhizobium (9.21%), Bradyrhizobium (5.05%), and Labrys (4.75%). The proportion of Hp-I infection was significantly higher in CAG patients (91.1%) than in nCAG patients (71.0%) (P < 0.001). The gastric microbiota richness index (observed OTUs, Chao) was significantly lower in CAG patients than in nCAG patients (P <0.05). Compared with avirulent Hp-II infection, virulent Hp-I infection significantly decreased the Shannon index in CAG patients (P <0.05). In nCAG patients, Hp-I infected patients had lower abundances of several dominant gastric bacteria (Aliidiomarina, Reyranella, Halomonas, Pseudomonas, Acidovorax) than Hp-II infected patients.Meanwhile, in CAG patients, Hp-Ⅰ infected patients occupied lower abundances of several dominant oral bacteria (Neisseria, Staphylococcus and Haemophilus) than Hp-II infected patients.In addition, bile reflux significantly promoted the colonization of dominant oral microbiota (Veillonella, Prevotella 7 and Rothia) in the stomach of CAG patients. There was no significant symbiotic relationship between Helicobacter bacteria and non-Helicobacter bacteria in the 2 stomach of nCAG patients, while Helicobacter bacteria distinctly linked with the non-Helicobacter bacteria (Pseudolabrys, Ralstonia, Bradyrhizobium, Mesorhizobium and Variovorax) in CAG patients.Virulent Hp infection alters the gastric microbiota, reduces microbial diversity, and enhances the symbiotic relationship between the Helicobacter bacteria and non-Helicobacter bacteria in patients with chronic gastritis. The data provides new evidence for treating Hp infection by improving the gastric microbiota.